How to Do Everyday Jobs Better and Easier with Plastics Housewares - Dow Chemical Company (1957)
Color print advertisement for Styron, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications, including packaging and food service, appliances, and other plastic wares. The advertisement features an illustration of a mother and son framed by assorted housewares made of Styron. This advertisement appeared in a 1957 edition of Ladies' Home Journal.
Keywords: Plastics; Chemical industry; Housewives; Dow Chemical Company; Housewives as consumers; Women in advertising; Advertising; Parent and child; Plastics industry and trade; Corporations